Mutational analysis of MSX1 and PAX9 genes in Portuguese families with maxillary lateral incisor agenesis - Pinho, Teresa (2010)
The observation that certain patterns of tooth agenesis occur more frequently in individuals of the same family may suggest the existence of predisposing genetic factors. The aim of this study was to search for mutations in the PAX9 and MSX1 genes and to investigate their potential association with the maxillary lateral incisor agenesis (MLIA) phenotype in 12 Portuguese families, a total of 52 individuals, 12 probands and 40 relatives (eight of which had MLIA). Twenty-three of the subjects were male and 29 female with an age range of 10-75 years. The control group comprised random DNA samples of 91 Portuguese individuals. Nucleotide alterations were not detected in the coding regions of the MSX1 gene, analysed by single-strand conformation polymorphism and sequencing; in the PAX9 gene, a polymorphism was found that led to transition of G718 to C, implying a change of alanine 240 for proline. However, the differences in the frequencies of the PAX9 gene polymorphism between the probands (67 per cent) and the control population (56 per cent carrying the c allele) were not statistically significant as determined by chi-square test, and the polymorphism did not clearly segregate with the trait in the families. Aggregating the available data, there does not seem to exist a clear association between the alanine 240 for proline variant in the PAX9 gene and the MLIA phenotype. Further studies are required to clarify the basic genetics of MLIA.